Lysophosphatidic acid signaling in ovarian cancer. (2nd November 2015) - Jesionowska, Anna; Cecerska-Heryc, Elzbieta; Matoszka, Natalia; Dolegowska, Barbara
Abstract: Lysophosphatidic acid (LPA) is a bioactive phospholipid that is involved in signal transduction between cells. Plasma and ascites levels of LPA are increased in ovarian cancer patients even in the early stages and thus LPA is considered as a potential diagnostic marker for this disease. This review presents the current knowledge regarding LPA signaling in epithelial ovarian cancer. LPA stimulates proliferation, migration and invasion of ovarian cancer cells through regulation of vascular endothelial growth factor, matrix metalloproteinases, urokinase plasminogen activator, interleukin-6, interleukin-8, CXC motif chemokine ligand 12/CXC receptor 4, COX2, cyclin D1, Hippo-Yap and growth-regulated oncogene α concentrations. In this article, all of these targets and signal pathways involved in LPA influence are described.